TRENDS IN DIFFERENTIATED LEARNING IN ELEMENTARY SCHOOLS (2015-2025): A SYSTEMATIC LITERATURE REVIEW - Redhatul Fauzia; Endang Susilaningsih; Bambang Subali; Ellianawati Ellianawati (Jurnal Cakrawala Pendas, 2026)
Differentiated learning is gaining attention in elementary education in Indonesia, especially after the implementation of the Merdeka Curriculum. This study examines publication trends, implementation patterns, obstacles, and strategies for strengthening differentiated learning at the elementary school level during the period 2015–2025. The study was conducted using the Systematic Literature Review (SLR) method based on the PRISMA 2020 protocol. A total of 25 empirical research articles that met the inclusion criteria were systematically analyzed. The results of the study show that the development of differentiated learning can be divided into three main phases: (1) the pre-pandemic period, when its implementation was still limited because teachers' pedagogical abilities were not yet optimal; (2) the pandemic period, when differentiated learning began to adapt to online learning models; and (3) the Merdeka Curriculum era, when diagnostic assessments, personalized learning, and student learning profile mapping were further strengthened. Bibliometric mapping using VOSviewer revealed dominant topics such as readiness-based learning, flexible learning, the use of digital media, and social-emotional support. In general, differentiated learning has been proven to increase student motivation, participation, and academic achievement; however, obstacles related to teacher readiness, time management, and infrastructure availability are still encountered. This study presents new insights by mapping trends over a decade based on policy phases, while combining empirical synthesis and bibliometric visualization. Recommendations are also provided for research and policy development so that the implementation of differentiated learning in elementary schools can be more evenly distributed.